"I Couldn't Find Information for People with Pets; So, I Gave Up, ": Pet Owner Identity, Informational Needs, and Media Uses during Hurricane Harvey. Issue 1 (1st January 2023) - Day, Ashleigh M.; Novak, Julie M.
Abstract : Many pet owners consider their pets to be family. During disasters, this could be problematic because pet owners face unique challenges and, thus, may have unique communicative exigencies. This research queries how pet owner identity may impact informational needs, media uses, and informational sources in the context of Hurricane Harvey. Data were gathered using a three-stage, mixed-method design that sampled from Harvey-affected pet owners. Findings suggest that pet owner identity influenced informational needs and subsequent media uses and sources. Findings highlight the importance of targeted crisis communication and preparedness. Implications are discussed related to research, theory, and praxis.